Intermediate fire severity diversity promotes richness of forest carnivores in California. (17th August 2021) - Furnas, Brett J.; Goldstein, Benjamin R.; Figura, Peter J.
Abstract: Aim: Fire can strongly influence ecosystem function, and human activities are disrupting fire activity at the global scale. Ecological theory and a growing body of literature suggest that a mixed severity fire regime promotes biodiversity in western North America. Some researchers advocate the use of pyrodiversity (i.e. heterogeneity in aspects of the fire regime such as time since fire or severity) as a conservation index to be maximized. Others caution against this approach arguing that the index oversimplifies fire–biodiversity interactions across trophic, spatial and temporal scales. We evaluated the effects of several landscape‐scale pyrodiversity indices, and their severity and time‐since‐fire components, on species richness of forest carnivores. Location: Northern California, United States. Methods: We gathered data on fire history and mammal occurrence from camera trap surveys at 1, 451 sites across Northern California public and private forestlands during 2009–2018. We used these data to model the effects of fire severity diversity, and its components (i.e. low, moderate and high severity wildfires), on carnivore richness at short (10 years) and longer (25 years) timeframes. We repeated the modelling using a measure of time‐since‐fire diversity and its components (<10 years, 10–20 years, 20–30 years, 30–40 years, 40–100 years). We used Bayesian multispecies occupancy modelling to correct for imperfect measurement of species richness. Results: We found that carnivore richness was highest at locations with intermediate fire severity diversity (0.46, 90%CI: 0.40–0.52) calculated using Simpson's Measure of Evenness (range: 0–1) for the 10‐year timeframe, and the results were almost identical yet less precise for the longer timeframe. When we separated fire severity diversity into its components, we found that carnivore richness was highest at locations where 17% (90%CI: 4–20) of the landscape had experienced low severity burns over the past decade. In contrast, we found no association between time‐since‐fire diversity and carnivore richness, however, an intermediate amount of one of the components (e.g., the total amount of fire in the past 10 years) was positively associated with carnivore richness. Our results are consistent with a mixed severity fire regime wherein there is a greater extent of low severity than high severity fire. Main conclusions: Overall our results suggest that carnivores would benefit from landscapes managed for greater, but not maximal, fire severity diversity. Our results also suggest that prescribed, low severity burns may provide ecological services to wildlife not otherwise provided by silviculture in a managed forest landscape.